An investigation on the role of Visual Merchandising Displays in the promotion of traditional fabrics. An evidence from retailing the Asante Kente fabrics in Ghana - Ofori-Okyere, Isaac; Kweku, Safo Ankama (Archives of Business Research, 2016)
The fierce competition and the similarity of competing merchandise characterised modern fashion industry impel apparel retailers to utilise various visual merchandising displays (VMDs) to improve the desirability of their products and to achieve differentiation of their offerings from competition. This has led to this study investigating on the role played by the various VMDs in the promotion of Asante Kente apparels by reviewing literature on: the Kente apparel, various VMDs adopted by retailers to promote products, and benefits derived by apparel retailers from adopting VMDs. An explorative research and qualitative data were gathered by means of projected images and focus groups discussions and direct observations. The data were analysed by means of thematic analysis. Findings indicated that respondents have knowledge on certain VMDs both exterior and in-store, whereas, other VMDs were considered not appropriate in their line of business. This is to say that all the respondents contacted on the field agreed to certain positions established by extant theories regarding the adoption of VMDs and the role they play in promoting apparels in retail shops